Effect of Pranic Healing on sleep quality in primary insomnia: An exploratory study - G. N. Santhosh; Prashanth Shetty; Geetha B. Shetty; Balakrishna Shetty; H. L. Nanjeshgowda (Yoga-Mimamsa)
Background: Insomnia, characterized by difficulty in falling or staying asleep, significantly impacts daily functioning despite adequate sleep opportunities, affecting physical, mental, social health, and professional life. Pranic Healing (PH) is an age-old therapeutic modality focused on the energy fields that surround and reside inside the human body. This study aimed to evaluate the effects of PH on sleep quality in individuals with insomnia. Methods: Fifteen eligible subjects completed the study by receiving 7 PH sessions for 2 weeks for 30 min. The Pittsburgh Sleep Quality Index (PSQI) was assessed at baseline and postintervention before administering the prandial healing treatment. Results: After 2 weeks of PH, it was revealed that of the six components of the PSQI, subjective sleep quality (p < 0.001), sleep latency (p < 0.005), sleep duration (p < 0.004), and daytime dysfunction (p < 0.04) improved significantly, and SCI (p < 0.001). However, changes in sleep efficiency (p = 0.82) and sleep disturbances (p = 0.06) were not significant. Overall, there was a significant improvement in the quality of sleep in subjects diagnosed with insomnia. Conclusion: PH has shown promise for improving sleep quality in patients with insomnia through its influence of pranic energy. However, further long-term randomized controlled studies are needed to determine the results and mechanism of action involved.